A framework for assessing the trustworthiness of scientific research findings - Brian A. Nosek; David B. Allison; Kathleen Hall Jamieson; Marcia McNutt; A. Beau Nielsen; Susan M. Wolf (Proceedings of the National Academy of Sciences, 2026)
Vigorous debate has erupted over the trustworthiness of scientific research findings in a number of domains. The question “what makes research findings trustworthy?” elicits different answers depending on whether the emphasis is on research integrity and ethics, research methods, transparency, inclusion, assessment and peer review, or scholarly communication. Each provides partial insight. We offer a systems approach that focuses on whether the research is accountable, evaluable, well-formulated, has been evaluated, controls for bias, reduces error, and whether the claims are warranted by the evidence. We tie each of these components to measurable indicators of trustworthiness for evaluating the research itself, the researchers conducting the research, and the organizations supporting the research. Our goals are to offer a framework that can be applied across methods, approaches, and disciplines and to foster innovation in development of trustworthiness indicators. Developing valid indicators will improve the conduct and assessment of research and, ultimately, public understanding and trust.